Variations of mesozooplankton composition in a eutrophicated semi-enclosed system (Encerrada bay, Tierra del Fuego, Argentina) - Biancalana, Florencia (2011)
The aim of the present study was to analyze EB mesozooplankton composition in the light of the physico-chemical parameters of the water column. Particular attention was paid to the presence of opportunistic species which adapt favourably to EB´s environmental conditions.